Pengelolaan Media Sosial sebagai Strategi Pemasaran Digital pada Pengembangan Pariwisata Halal di Gampong Keude Unga - Ega Dwi Sahputri; Siti Sarah; Aulia Ari Ananda; Rizki Dani Kusuma; Fani Hatja Nurhayati; Salman Abdul Muthalib (Jurnal Riset dan Pengabdian Masyarakat, 2023)
Halal tourism continues to be a hot topic and a profitable business around the world, including in Indonesia. Keude Unga, one of the villages located in the district of Aceh Jaya, Aceh is an area that has several tourist attractions such as lhok keutapang beach, batee cap, and the tomb of the famous ulama 'meurehom unga'. However, some of these attractions were not widely promoted by the gampong community due to the lack of knowledge in using social media so that these attractions were not known by the society. Therefore, the purpose of this study is to analyze the effectiveness of the use of social media (instagram, tiktok and youtube) and conventional media (pamphlets) in increasing the number of visitors at the three tourist attractions mentioned above. This research is a qualitative research with a case study approach, namely interviews, participant observation, and document records. The results showed that there was a significant increase in visitors to the lhok keutapang beach and the meurehom unga tomb both from within and outside the area with pamphlets on the lhok keutapang beach and the social media account on the instagram platform @pesona_keude_unga. In addition, the strategies that support the effectiveness of social media used are content creation, platform determination, program planning, program implementation, monitoring and evaluation